A treacherous paradise - Mankell, Henning, 1948-2015 (Alfred A. Knopf, 2013)
Cold and poverty define Hanna Renstrom's childhood in remote northern Sweden, and in 1905, at nineteen, she boards a ship for Australia in hope of a better life. But none of her hopes--or fears--prepares her for the life she will lead. After two brief marriages, she finds herself a widow twice over, and the owner of a bordello in Portuguese East Africa, a world where colonialism and white supremacy rule, where she is isolated within society by her profession and her sex, and, among the bordello's black prostitutes, by her color. As Hanna's story unfurls over the next several years, we watch her in this "treacherous paradise," as she wrestles with a constant, wrenching loneliness and with the racism she's meant to unthinkingly adopt. And as her life becomes increasingly intertwined with the prostitutes, she moves inexorably toward the moment when she will make a decision that defies every expectation society has of her, and, more important, those she has of herself.